PENGARUH GAYA KEPEMIMPINAN PARTISIPATIF TERHADAP ORGANIZATIONAL TRUST DAN KOMITMEN ORGANISASI SERTA DAMPAKNYA TERHADAP KINERJA PEGAWAI - Mirdha Fahlevi SI; Affandi Affandi (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2019)
This study examines the relationship between participative leadership and employee in role performance in public sector, with mediating role of organizational trust and organizational commitment. Data were collected from 276 employees in several goverment agencies of republic of Indonesia. Convenience sampling method is used to collect the data from responden. This research used path analysis to analyze the data. Based on the reseach finding, participative leadership directly impact on employee in role performance. In addition,organizational trust and organizational commitment does not mediate the relationship beetwen dependen and independen variable. The results showed participative leadership will be improved employee in role performance in goverment agencies. Key words : Participative Leadership, In role Performance, employee